Bridging the Gap: VR Applications for Both Inpatients and Outpatients in Long-Term Care - Farrugia, Jason (Magyar Gerontológia, 2024)
Virtual reality technology is increasingly utilised in long-term care to enhance patient engagement and improve outcomes. This presentation focuses on the integration of virtual reality in occupational therapy for both inpatients and outpatients at St Vincent de Paul Long-Term Care Facility, particularly for individuals recovering from stroke and those with Parkinson’s disease.